A Prodigy of Universal Genius: Robert Leslie Ellis, 1817-1859 - Verburgt, Lukas M. (Studies in History and Philosophy of Science, 2022)
Places Ellis at the heart of early-Victorian Cambridge with in-depth descriptions on his scientific work and tragic life Provides a unique glimpse into Victorian intellectual culture, based on previously unpublished archival materials This open access book brings together for the first time all aspects of the tragic life and fascinating work of the polymath Robert Leslie Ellis (1817-1859), placing him at the heart of early-Victorian intellectual culture. Written by a diverse team of experts, the chapters in the book's first part contain in-depth examinations of, among other things, Ellis's family, education, Bacon scholarship and mathematical contributions. The second part consists of annotated transcriptions of a selection of Ellis's diaries and correspondence. Taken together, A Prodigy of Universal Genius: Robert Leslie Ellis, 1817-1859 is a rich resource for historians of science, historians of mathematics and Victorian scholars alike. Robert Leslie Ellis was one of the most intriguing and wide-ranging intellectual figures of early Victorian Britain, his contributions ranging from advanced mathematical analysis to profound commentaries on philosophy and classics and a decisive role in the orientation of mid-nineteenth century scholarship. This very welcome collection offers both new and authoritative commentaries on the work, setting it in the context of the mathematical, philosophical and cultural milieux of the period, together with fascinating passages from the wealth of unpublished papers Ellis composed during his brief and brilliant career. - Simon Schaffer, Department of History and Philosophy of Science, University of Cambridge